Fostering Green Innovation and Environmental Consciousness: A Pathway to Competitive Advantage in the Green Economy. - Fahrul Riza; Dewi Sumarti (School of Postgraduate Studies, Diponegoro Univer, 2024)
This research aims to identify the preceding factors for achieving green competitive advantage, as traditional marketing might not be adequate to cater to this aspect. Therefore, the analysis explores the correlation between the theory of reasoned action and green marketing and how the blending of these concepts affects eco-friendly innovation and, subsequently, green competitive advantage. A quantitative approach was employed to conduct this investigation, using questionnaires gathered through direct visits to 100 coffee shops in and around Jakarta. The sample was selected through purposive non-probability sampling. The collected data were analyzed using SMART PLS.3 software, employing the structural equation model (SEM). The findings highlight that both internal and external orientations exert an impact on green innovation, which, in turn, affects green competitive advantage. However, it should be noted that internal and external environmental orientations do not have a direct impact on green competitive advantage. This research contributes to the field of green marketing by highlighting the crucial role of green innovation in achieving green competitive advantage and establishing the link between environmental orientation and competitive edge. Companies can allocate resources to improve their green innovation efforts, which can strengthen their competitive position in the market. The study provides practical guidance for businesses aiming to enhance their green competitive advantage. However, the identified limitations should prompt researchers and practitioners to consider broader industry and methodology coverage in future investigations.